High-voltage electrolyte and lithium ion battery
By using compounds containing benzene ring and cyano functional groups in lithium-ion batteries to form a stable surface film, the problem of oxidation and decomposition reaction of the electrolyte at high voltage is solved, and the cycle life and high temperature performance of the battery are improved.
Patent Information
- Application Number
- CN202411555550.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-03
AI Technical Summary
At high voltage, existing lithium-ion batteries are easily oxidized and decomposed by carbonate electrolytes, resulting in a decline in battery performance, limiting the energy density and cycle life of lithium batteries.
Using a high voltage electrolyte, including lithium salts, non-aqueous solvents, phthalic acid derivatives containing benzene ring functional groups and cyano functional groups, the phenylborate esters compound is formed by complexing or physical bonding. The surface film suppresses the side effects of the electrolyte reaction product, improves the compatibility between the electrolyte and the graphite negative electrode, and forms a protective film at the interface between the positive and negative electrodes.
It significantly improves the cycle life of lithium-ion batteries under high voltage, improves the initial impedance of the battery cell, reduces the impedance growth rate, improves the battery capacity recovery rate, suppresses gas production problems, and enhances the battery's high-temperature storage performance and long-term Cyclic stability.
Smart Images

Figure BDA0005116322680000021 
Figure BDA0005116322680000022 
Figure BDA0005116322680000031
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a high voltage electrolyte and a lithium ion battery. Background Art
[0002] Since the 1990s, with the growing demand for high-energy-density batteries in portable electronic devices, new energy vehicles, and large-scale grid energy storage equipment, lithium batteries have become a new generation of energy storage equipment due to their significant advantages such as high energy density, high power density, long cycle life, and green environmental protection. However, insufficient battery life is the biggest obstacle to its large-scale application. Therefore, improving the energy density of lithium batteries is the biggest guarantee for improving consumers' recognition and purchasing power for new energy vehicles.
[0003] Increasing the working voltage of cathode materials is one of the effective ways to increase the energy density of lithium-ion batteries. However, the carbonate electrolytes currently used are prone to oxidative decomposition reactions on the surface of cathode materials under high voltage, resulting in decreased battery performance. Therefore, there is an urgent need to develop a new electrolyte system suitable for high-voltage lithium batteries. Summary of the invention
[0004] Based on the technical problems existing in the background technology, the present invention proposes a high-voltage electrolyte and a lithium-ion battery.
[0005] The invention provides a high voltage electrolyte comprising a lithium salt, a non-aqueous solvent, a first additive and a second additive; the first additive comprising a phthalic acid derivative containing a benzene ring functional group and / or a phenylboronic acid pinacol ester compound containing a cyano functional group.
[0006] The phthalic acid derivative containing a benzene ring functional group has a structural formula as shown in Formula I:
[0007]
[0008] In the formula I, R1 to R4 are selected from hydrogen atoms, halogen atoms, benzene rings, substituted or unsubstituted C 1~5 Any one of alkyl, alkenyl and alkynyl, and at least one of R1 to R4 is a functional group containing a benzene ring.
[0009] The phenylboronic acid pinacol ester compound containing a cyano functional group has a structural formula as shown in Formula II:
[0010]
[0011] In the formula II, R5 to R9 are each independently selected from a hydrogen atom, a halogen atom, a cyano group, a benzene ring, a substituted or unsubstituted C 1~5Any one of alkyl, alkenyl and alkynyl, and at least one of R5 to R9 is a cyano-containing functional group.
[0012] The raw materials in the high-voltage electrolyte of the present invention act synergistically, and the obtained high-voltage electrolyte can improve the cycle life of the battery under high voltage. The present invention combines nitrile additives and anhydride compounds, and through complexation or physical combination or bonding, can form a stable surface film on the positive and negative electrodes, inhibit the side effects of the electrolyte reaction products, improve the compatibility of the electrolyte and the graphite negative electrode, and improve the cycle life of the battery under high voltage; at the same time, improve the initial impedance of the battery cell, reduce the impedance growth rate, improve the battery capacity recovery rate, inhibit the gas production problem, and improve the high-temperature storage performance and long-term cycle stability of the battery.
[0013] Preferably, the compound represented by formula I is selected from compound 1 to compound 3:
[0014]
[0015] Among them, compound 1 is 4-phenylethynylphthalic anhydride (CAS: 119389-05-8), compound 2 is tetraphenylphthalic anhydride (CAS: 4741-53-1), and compound 3 is 4-phenoxyphthalic anhydride (CAS: 21345-01-7).
[0016] Phthalic acid derivatives contain both benzene rings and anhydride functional groups, of which the benzene ring can undergo electropolymerization to form a film at the positive electrode, which can effectively protect the positive electrode interface, inhibit the migration of transition metal ions at the positive electrode under high voltage conditions and the direct contact between the electrode interface and the electrolyte, and improve the high-temperature storage performance and cycle stability of the battery. The anhydride is easy to undergo a reduction film-forming reaction at the negative electrode interface, forming a stable SEI film at the negative electrode interface, isolating the direct contact between the electrolyte and the electrode interface, alleviating the consumption of the electrolyte, and reducing the irreversible loss of active lithium at the negative electrode interface under high temperature conditions, thereby improving the high-temperature performance of the battery.
[0017] Preferably, the compound represented by formula II is selected from compound 4 to compound 6:
[0018]
[0019]
[0020] Among them, compound 4 is 4-cyano-2-fluoro-5-methylphenylboronic acid pinacol ester (CAS: 1192023-08-7), compound 5 is 4-(cyanomethyl)phenylboronic acid pinacol ester (CAS: 138500-86-4), and compound 6 is 4-(4-cyanophenyl)phenylboronic acid pinacol ester (CAS: 406482-72-2).
[0021] Since the carbon-nitrogen triple bond energy in the cyanide group of nitrile additives is very high and not easily oxidized, nitrile additives have good stability on the positive electrode. At the same time, the cyanide group has a strong coordination ability and can combine with the active sites on the electrode surface, masking the active ions on the positive electrode surface, reducing the decomposition of the electrode on the electrolyte, forming a low-impedance CEI film, and improving the cycle life of the battery at high voltage. In addition, nitrile additives have a wide electrochemical window, are more stable at high voltage, and have better performance.
[0022] Preferably, the mass ratio of the compound of formula I to the compound of formula II is (0.5-1.5):(1.5-2.5).
[0023] Preferably, the mass of the first additive accounts for 0.1-10% of the total mass of the electrolyte.
[0024] Preferably, the lithium salt is selected from one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium dioxalatoborate, lithium difluorooxalatoborate, lithium difluorooxalatophosphate, lithium bis(fluorosulfonyl)imide salt, and lithium bis(trifluoromethylsulfonyl)imide.
[0025] The synergistic effect of multiple lithium salts can effectively improve the battery coulombic efficiency and achieve uniform deposition of metallic lithium. By optimizing the lithium salt ratio, the ionic conductivity can be improved and the stable deposition of metallic lithium can be achieved.
[0026] Preferably, the mass of the lithium salt accounts for 10-20% of the total mass of the electrolyte.
[0027] Preferably, the second additive is selected from at least one of a low-temperature additive and an anti-overcharge additive.
[0028] Preferably, the second additive is selected from at least one of fluoroethylene carbonate, vinyl sulfate, tris(trimethylsilyl)phosphate, tris(trimethylsilyl)borate, lithium difluorophosphate and 1,3-propane sultone.
[0029] Preferably, the mass of the second additive accounts for 1-5% of the total mass of the electrolyte.
[0030] The second additive works synergistically with the first additive to increase the cycle life of the battery at high voltage, inhibit gas production problems, and improve the battery's high temperature storage performance and long-term cycle stability.
[0031] Preferably, the non-aqueous solvent includes at least two of a chain carbonate solvent, a cyclic carbonate solvent, and a carboxylate solvent; the cyclic carbonate solvent includes at least one of ethylene carbonate, fluoroethylene carbonate, and propylene carbonate; the chain carbonate solvent includes at least one of dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate; the carboxylate solvent includes at least one of propyl acetate, ethyl acetate, and propyl propionate.
[0032] Cyclic carbonates have a higher dielectric constant but a higher viscosity, while chain carbonates have a relatively lower viscosity but a lower dielectric constant than cyclic carbonates. Taking into account the non-aqueous solvent comprising at least one of the cyclic carbonates and at least one of the chain carbonates, a mixed solvent takes into account the requirements of both dielectric constant and viscosity.
[0033] A lithium ion battery comprises a positive electrode, a negative electrode, a separator and the above-mentioned high-voltage electrolyte.
[0034] Preferably, the active material of the positive electrode is a nickel-cobalt-manganese ternary material or a nickel-cobalt-aluminum ternary material.
[0035] Preferably, the active material of the negative electrode is graphite or silicon-carbon material.
[0036] The beneficial effects of the present invention are:
[0037] The present invention combines nitrile additives and acid anhydride compounds to form stable surface films on positive and negative electrodes through complexation, physical combination or bonding, thereby inhibiting the side effects of electrolyte reaction products, improving the compatibility of electrolyte and graphite negative electrode, and increasing the cycle life of the battery under high voltage. At the same time, the initial impedance of the battery cell is improved, the impedance growth rate is reduced, the battery capacity recovery rate is increased, the gas production problem is inhibited, and the high-temperature storage performance and long-term cycle stability of the battery are improved. DETAILED DESCRIPTION
[0038] The technical solution of the present invention is described in detail through specific embodiments.
[0039] Unless otherwise specified, the materials, reagents, etc. used in the following examples and comparative examples can be obtained from commercial sources.
[0040] Example 1
[0041] Preparation of high voltage electrolyte:
[0042] In a glove box filled with argon (water content <0.1ppm, oxygen content <0.1ppm), ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed at a mass ratio of EC:EMC:DEC=2:3:5 to obtain a solvent; lithium hexafluorophosphate (LiPF6) is slowly added to the solvent, and after LiPF6 is completely dissolved, tris(trimethylsilyl) phosphate (TMSP), fluoroethylene carbonate (FEC) and compound 2 are added to obtain;
[0043] The raw materials of the high voltage electrolyte are composed of the following components in percentage by mass: 13% lithium hexafluorophosphate (LiPF6), 1.0% tris(trimethylsilyl) phosphate (TMSP), 1.0% fluoroethylene carbonate (FEC) and 0.5% compound 2, and the solvent is supplemented to 100%.
[0044] Preparation of positive electrode:
[0045] The active material lithium nickel cobalt manganese oxide (NCM811), the conductive agent super conductive carbon (SP), and the binder polyvinylidene fluoride (PVDF) were fully stirred and mixed in a solvent N-methyl-2-pyrrolidone at a mass ratio of 97:1:2. The obtained slurry was coated on the current collector Al foil, and the positive electrode sheet was obtained by slitting, die cutting, and rolling. The compaction density is 3.45g / cm 3 .
[0046] Preparation of negative electrode sheet:
[0047] The silicon carbon negative electrode (SiOC600), conductive agent super conductive carbon (SP), binder styrene butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) were fully stirred and mixed in a solvent deionized water at a mass ratio of 95:1:2:2, and the obtained slurry was coated on the current collector Cu foil. After slitting, rolling, and die cutting, the negative electrode sheet was obtained, and its compaction density was 1.6g / cm 3 .
[0048] Preparation of lithium-ion batteries:
[0049] The positive electrode sheet, the separator (the separator used is a polypropylene PP film coated with a nano-aluminum oxide coating, wherein the thickness of the PP film is 12 μm and the thickness of the nano-aluminum oxide coating is 4 μm), and the negative electrode sheet are stacked in sequence to obtain a bare cell according to the process of stacked batteries, and then the bare cell is pre-packaged in an aluminum-plastic film, injected with the prepared high-voltage electrolyte, and then packaged to obtain the required soft-pack battery.
[0050] Example 2
[0051] Preparation of high voltage electrolyte:
[0052] In a glove box filled with argon (water content <0.1ppm, oxygen content <0.1ppm), ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed at a mass ratio of EC:EMC:DEC=2:3:5 to obtain a solvent; lithium hexafluorophosphate (LiPF6) is slowly added to the solvent, and after LiPF6 is completely dissolved, tris(trimethylsilyl) phosphate (TMSP), fluoroethylene carbonate (FEC) and compound 2 are added to obtain;
[0053] The raw materials of the high voltage electrolyte are composed of the following components in percentage by mass: 13% lithium hexafluorophosphate (LiPF6), 1.0% tris(trimethylsilyl) phosphate (TMSP), 1.0% fluoroethylene carbonate (FEC) and 1% compound 2, and the solvent is supplemented to 100%.
[0054] The preparation methods of the positive electrode sheet, the negative electrode sheet and the battery are the same as those in Example 1.
[0055] Example 3
[0056] Preparation of high voltage electrolyte:
[0057] In a glove box filled with argon (water content <0.1ppm, oxygen content <0.1ppm), ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed at a mass ratio of EC:EMC:DEC=2:3:5 to obtain a solvent; lithium hexafluorophosphate (LiPF6) is slowly added to the solvent, and after LiPF6 is completely dissolved, tris(trimethylsilyl) phosphate (TMSP), fluoroethylene carbonate (FEC) and compound 2 are added to obtain;
[0058] The raw materials of the high voltage electrolyte are composed of the following components in percentage by mass: 13% lithium hexafluorophosphate (LiPF6), 1.0% tris(trimethylsilyl) phosphate (TMSP), 1.0% fluoroethylene carbonate (FEC) and 3% compound 2, and the solvent is supplemented to 100%.
[0059] The preparation methods of the positive electrode sheet, the negative electrode sheet and the battery are the same as those in Example 1.
[0060] Example 4
[0061] Preparation of high voltage electrolyte:
[0062] In a glove box filled with argon (water content <0.1ppm, oxygen content <0.1ppm), ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed at a mass ratio of EC:EMC:DEC=2:3:5 to obtain a solvent; lithium hexafluorophosphate (LiPF6) is slowly added to the solvent, and after LiPF6 is completely dissolved, tris(trimethylsilyl) phosphate (TMSP), fluoroethylene carbonate (FEC) and compound 5 are added to obtain;
[0063] The raw materials of the high voltage electrolyte are composed of the following components in percentage by mass: 13% lithium hexafluorophosphate (LiPF6), 1.0% tris(trimethylsilyl) phosphate (TMSP), 1.0% fluoroethylene carbonate (FEC) and 0.5% compound 5, and the solvent is supplemented to 100%.
[0064] The preparation methods of the positive electrode sheet, the negative electrode sheet and the battery are the same as those in Example 1.
[0065] Example 5
[0066] Preparation of high voltage electrolyte:
[0067] In a glove box filled with argon (water content <0.1ppm, oxygen content <0.1ppm), ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed at a mass ratio of EC:EMC:DEC=2:3:5 to obtain a solvent; lithium hexafluorophosphate (LiPF6) is slowly added to the solvent, and after LiPF6 is completely dissolved, tris(trimethylsilyl) phosphate (TMSP), fluoroethylene carbonate (FEC) and compound 5 are added to obtain;
[0068] The raw materials of the high voltage electrolyte are composed of the following components in percentage by mass: 13% lithium hexafluorophosphate (LiPF6), 1.0% tris(trimethylsilyl) phosphate (TMSP), 1.0% fluoroethylene carbonate (FEC) and 3% compound 5, and the solvent is supplemented to 100%.
[0069] The preparation methods of the positive electrode sheet, the negative electrode sheet and the battery are the same as those in Example 1.
[0070] Example 6
[0071] Preparation of high voltage electrolyte:
[0072] In a glove box filled with argon (water content <0.1ppm, oxygen content <0.1ppm), ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed at a mass ratio of EC:EMC:DEC=2:3:5 to obtain a solvent; lithium hexafluorophosphate (LiPF6) is slowly added to the solvent, and after LiPF6 is completely dissolved, tris(trimethylsilyl) phosphate (TMSP), fluoroethylene carbonate (FEC) and compound 5 are added to obtain;
[0073] The raw materials of the high voltage electrolyte are composed of the following components in percentage by mass: 13% lithium hexafluorophosphate (LiPF6), 1.0% tris(trimethylsilyl) phosphate (TMSP), 1.0% fluoroethylene carbonate (FEC) and 5% compound 5, and the solvent is supplemented to 100%.
[0074] The preparation methods of the positive electrode sheet, the negative electrode sheet and the battery are the same as those in Example 1.
[0075] Example 7
[0076] Preparation of high voltage electrolyte:
[0077] In a glove box filled with argon (water content <0.1ppm, oxygen content <0.1ppm), ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed at a mass ratio of EC:EMC:DEC=2:3:5 to obtain a solvent; lithium hexafluorophosphate (LiPF6) is slowly added to the solvent, and after LiPF6 is completely dissolved, tris(trimethylsilyl) phosphate (TMSP), fluoroethylene carbonate (FEC) and compound 2 and compound 5 are added to obtain;
[0078] Among them, the raw materials of the high-voltage electrolyte are composed of the following components in percentage by mass: 13% lithium hexafluorophosphate (LiPF6), 1.0% tris(trimethylsilyl) phosphate (TMSP), 1.0% fluoroethylene carbonate (FEC), 0.5% compound 2 and 2.5% compound 5, and the solvent is supplemented to 100%.
[0079] The preparation methods of the positive electrode sheet, the negative electrode sheet and the battery are the same as those in Example 1.
[0080] Example 8
[0081] Preparation of high voltage electrolyte:
[0082] In a glove box filled with argon (water content <0.1ppm, oxygen content <0.1ppm), ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed at a mass ratio of EC:EMC:DEC=2:3:5 to obtain a solvent; lithium hexafluorophosphate (LiPF6) is slowly added to the solvent, and after LiPF6 is completely dissolved, tris(trimethylsilyl) phosphate (TMSP), fluoroethylene carbonate (FEC) and compound 2 and compound 5 are added to obtain;
[0083] Among them, the raw materials of the high-voltage electrolyte are composed of the following components in percentage by mass: 13% lithium hexafluorophosphate (LiPF6), 1.0% tris(trimethylsilyl) phosphate (TMSP), 1.0% fluoroethylene carbonate (FEC), 1% compound 5 and 2% compound 5, and the solvent is supplemented to 100%.
[0084] The preparation methods of the positive electrode sheet, the negative electrode sheet and the battery are the same as those in Example 1.
[0085] Example 9
[0086] Preparation of high voltage electrolyte:
[0087] In a glove box filled with argon (water content <0.1ppm, oxygen content <0.1ppm), ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed at a mass ratio of EC:EMC:DEC=2:3:5 to obtain a solvent; lithium hexafluorophosphate (LiPF6) is slowly added to the solvent, and after LiPF6 is completely dissolved, tris(trimethylsilyl) phosphate (TMSP), fluoroethylene carbonate (FEC) and compound 2 and compound 5 are added to obtain;
[0088] Among them, the raw materials of the high-voltage electrolyte are composed of the following components in percentage by mass: 13% lithium hexafluorophosphate (LiPF6), 1.0% tris(trimethylsilyl) phosphate (TMSP), 1.0% fluoroethylene carbonate (FEC), 1.5% compound 2 and 1.5% compound 5, and the solvent is supplemented to 100%.
[0089] The preparation methods of the positive electrode sheet, the negative electrode sheet and the battery are the same as those in Example 1.
[0090] Comparative Example 1
[0091] The high voltage electrolyte of Comparative Example 1 is different from that of Example 1 only in that it does not contain Compound 2. The rest of the raw materials and preparation method are the same as those of Example 1.
[0092] Test example
[0093] (1) 60℃ high temperature shelf test
[0094] The experimental batteries in Examples 1 to 9 and Comparative Example 1 were divided into different capacities and then fixed in volume. They were placed in a constant temperature oven at 60°C for 28 days in a fully charged state. The discharge capacity and volume of the batteries at 0.33C before and after storage were tested, and the capacity retention rate, recovery rate and volume expansion rate after 28 days were calculated.
[0095] (2) 25℃ cycle test
[0096] The experimental batteries in Examples 1 to 9 and Comparative Example 1 were divided into different capacities and then fixed in volume. The batteries were then placed in a constant temperature cabinet at 25°C, charged to full charge at 0.5C, and discharged to empty at 1C for 200 cycles, and the capacity retention rate after 200 cycles was calculated.
[0097] The test results are shown in Table 1:
[0098] Table 1 Comparison of high shelf and cycle performance between examples and comparative examples
[0099]
[0100]
[0101] Compared with Comparative Example 1, it can be seen from Examples 1 to 3 that adding 1% of Compound 2 additive can significantly improve the battery's high-shelf retention rate and recovery rate, while reducing volume expansion, improving the battery's high-temperature performance, and improving the capacity retention rate after 200 cycles. This is because phthalic acid derivatives contain both benzene rings and anhydride functional groups, in which anhydrides are prone to undergo reduction film-forming reactions at the negative electrode interface, forming a stable SEI film at the negative electrode interface, isolating the direct contact between the electrolyte and the electrode interface, alleviating the consumption of the electrolyte, and reducing the irreversible loss of active lithium at the negative electrode interface under high temperature conditions, thereby improving the battery's high-temperature performance. The benzene ring can undergo electropolymerization film formation at the positive electrode, which can effectively protect the positive electrode interface, inhibit the migration of positive transition metal ions under high voltage conditions and the direct contact between the electrode interface and the electrolyte, and improve the battery's high-temperature storage performance and cycle stability.
[0102] Compared with Comparative Example 1, Examples 4 to 6 show that when the additive content of Compound 5 is 3%, the capacity retention rate and recovery rate after 28 days of high storage are most significantly improved. Similar to Compound 2, Compound 5 also contains a benzene ring functional group, which can form a stable interface. In addition, as a nitrile additive, the bond energy of the carbon-nitrogen triple bond in the cyanide group contained in Compound 5 is very high and is not easily oxidized. Therefore, nitriles have good stability on the positive electrode and a relatively wide electrochemical window, making them suitable as high-voltage electrolyte additives. At the same time, the cyanide group has a strong coordination ability and can combine with the active sites on the electrode surface to mask the active ions on the positive electrode surface, reduce the decomposition effect of the electrode on the electrolyte, form a low-impedance CEI film, and improve the cycle life of the battery at a high voltage of 4.45V.
[0103] Examples 7 to 9 are the combined use of two additives. It can be seen that the capacity retention rate and recovery rate are further improved after 28 days of high storage, indicating that the combination of nitrile additives and acid anhydride compounds has a synergistic effect. The combination of nitrile additives and acid anhydride compounds can form a stable surface film on the positive and negative electrodes through complexation or physical combination or bonding, inhibit the side effects of electrolyte reaction products, and improve the compatibility of electrolyte and graphite negative electrode. At the same time, it improves the initial impedance of the battery cell, reduces the impedance growth rate, improves the battery capacity recovery rate, inhibits gas production problems, and improves the high temperature storage performance and long-term cycle stability of the battery.
[0104] Compared with Example 5, Examples 7 to 9 use the same amount of additives, except that a combination of Compounds 2 and 5 is used. It can be seen that after the two compounds are combined in different proportions, the improvement effects of capacity retention and recovery rate after 28 days of high storage are better than those of a single compound, and the performance is optimal when the mass ratio of Compound 2 to Compound 5 is 1:1. After 28 days, the capacity retention rate is increased by 6.3% compared with Compound 5, and the recovery rate is increased by 5.5%. At the same time, gas production is further suppressed, and the volume expansion rate is reduced by 7.5%. In addition, the cycle retention rate is improved by 3% on the basis of Compound 5. It can be seen that the synergistic effect can be maximized only by continuously optimizing the content and ratio between the two types of additives.
[0105] In summary, the electrolyte provided by the present invention helps to improve the cycle life of the battery under high voltage; at the same time, it improves the initial impedance of the battery cell, reduces the impedance growth rate, increases the battery capacity recovery rate, inhibits gas production problems, and improves the high-temperature storage performance and long-term cycle stability of the battery.
[0106] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A high voltage electrolyte, characterized in that: The invention comprises a lithium salt, a non-aqueous solvent, a first additive and a second additive; the first additive comprises a phthalic acid derivative containing a benzene ring functional group and / or a phenylboronic acid pinacol ester compound containing a cyano functional group; The phthalic acid derivative containing a benzene ring functional group has a structural formula as shown in Formula I: In the formula I, R1 to R4 are selected from hydrogen atoms, halogen atoms, benzene rings, substituted or unsubstituted C 1~5 Any one of alkyl, alkenyl and alkynyl, and at least one of R1 to R4 is a functional group containing a benzene ring; The phenylboronic acid pinacol ester compound containing a cyano functional group has a structural formula as shown in Formula II: In the formula II, R5 to R9 are each independently selected from a hydrogen atom, a halogen atom, a cyano group, a substituted or unsubstituted C 1~5 Any one of an alkyl group, an alkenyl group, an alkynyl group, and a benzene ring, and at least one of R5 to R9 is a cyano-containing functional group.
2. The high voltage electrolyte according to claim 1, characterized in that: The compound represented by formula I is selected from compound 1 to compound 3:
3. The high voltage electrolyte according to claim 1, characterized in that: The compound represented by formula II is selected from compound 4 to compound 6:
4. The high voltage electrolyte according to claim 1, characterized in that: The mass ratio of the compound of formula I to the compound of formula II is (0.5-1.5):(1.5-2.5).
5. The high voltage electrolyte according to claim 1, characterized in that: The mass of the first additive accounts for 0.1-10% of the total mass of the electrolyte.
6. The high voltage electrolyte according to claim 1, characterized in that: The lithium salt is selected from one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium dioxalate borate, lithium difluorooxalate borate, lithium difluorooxalate phosphate, lithium bis(fluorosulfonyl imide), and lithium bis(trifluoromethylsulfonyl imide).
7. The high voltage electrolyte according to claim 1, characterized in that: The second additive is selected from at least one of fluoroethylene carbonate, vinyl sulfate, tris(trimethylsilyl) phosphate, tris(trimethylsilyl) borate, lithium difluorophosphate and 1,3-propane sultone; the mass of the second additive accounts for 1-5% of the total mass of the electrolyte.
8. The high voltage electrolyte according to claim 1, characterized in that: The non-aqueous solvent includes at least two of chain carbonate solvents, cyclic carbonate solvents, and carboxylate solvents; the cyclic carbonate solvent includes at least one of ethylene carbonate, fluoroethylene carbonate, and propylene carbonate; the chain carbonate solvent includes at least one of dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate; the carboxylate solvent includes at least one of propyl acetate, ethyl acetate, and propyl propionate.
9. A lithium ion battery, characterized in that: The invention comprises a positive electrode, a negative electrode, a separator and the high-voltage electrolyte according to any one of claims 1 to 8.
Citation Information
Patent Citations
Non-aqueous electrolytic solution for secondary battery, and secondary battery including same
CN107210487A
High-nickel ternary anode material system battery electrolyte and lithium ion battery
CN108808071A
Imide additive containing a sulfonated side chain, electrolyte and lithium ion battery thereof
CN113097566A
Lithium ion battery electrolyte, additive of lithium ion battery electrolyte, lithium ion battery cell, lithium ion battery pack and application of lithium ion battery pack
CN114079083A
Electrolyte containing phthalic anhydride compound and lithium ion battery
CN114447431A
Cited By
High-voltage sodium electro-ester electrolyte adaptive to polyanionic positive electrode
CN122177936A
